As sepulturas escavadas na rocha de Contumil (Porto) - Silva, Antonio Manuel S P (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2020)
The occasional discovery, in 1943, of three rock-cut graves, near Contumil (Campanhã, Oporto), was reported in the daily press but did not subsequently attract the attention of researchers. The descriptions, illustrated by two photographs, refer to three anthropomorphic graves, listed by the author of the main articles with an old chapel of the invocation of São Martinho, documented since the 11th century. There is no information about the fate of that archaeological find, probably destroyed by the urbanization and construction works of the Bairro de Casas Económicas of São Roque da Lameira.